NEUROPSYCHOLOGICAL HELP FOR CHILDREN WITH DIFFICULTIES IN LEARNING MATHEMATICS - S. M. Vinnikova (Вестник Кемеровского государственного университета, 2013)
The aim of this paper is to reveal and to analyze the causes of children’s difficulties in learning mathematics, and to suggest several games designed to facilitate the processes of perception, analysis and comprehension of the material, and to increase children's interest in mathematics.